Ion channel profile of TRPM8 cold receptors reveals a novel role of TASK-3 potassium channels in thermosensation - Morenilla-Palao, Cruz (Cell Rep, 2014)
Animals sense cold ambient temperatures through the activation of peripheral thermoreceptors that express TRPM8, a cold- and menthol-activated ion channel. These receptors can discriminate a very wide range of temperatures from innocuous to noxious. The molecular mechanism responsible for the variable sensitivity of individual cold receptors to temperature is unclear. To address this question, we performed a detailed ion channel expression analysis of cold sensitive neurons, combining BAC transgenesis with a molecular profiling approach in FACS purified TRPM8 neurons. We found that TASK-3 leak potassium channels are highly enriched in a subpopulation of these sensory neurons. The thermal threshold of TRPM8 cold neurons is decreased during TASK-3 blockade and in mice lacking TASK-3 and, most importantly, these mice display hypersensitivity to cold. Our results demonstrate a novel role of TASK-3 channels in thermosensation, showing that a channel-based combinatorial strategy in TRPM8 cold thermoreceptors leads to molecular specialization and functional diversity.